IDENTIFIKASI BAKTERI PENGOKSIDASI BESI DAN SULFUR BERDASARKAN GEN 16S rRNA DARI LAHAN TAMBANG TIMAH DI BELITUNG - Dhewanti Puspitasari; Hendro Pramono; Oedjijono Oedjijono (Scripta Biologica, 2014)
Heavy metals contamination disturb balance and diversity of microorganism in soil. Microorganisms which can able to survive in those conditions are bacteria capable of oxidizing heavy metals. Identification based on 16S rRNA was used to determine characteristics and phylogenetic relationship of bacteria which can oxidize iron and sulphur in tin mining areas. The aim of this research was able to determine the bacterias characteristics isolated from tin mining areas and determine the phylogenetic relation of iron-sulphur oxidizing bacteria on tin mining soil in Belitung based on 16S rRNA sequences. This research was done using descriptive method, including isolation, morphological characterization, and identification based on 16S rRNA sequences. Morphology characterization includes colony and cell morphology through Gram staining. Molecular characterization includes amplification of 16S rRNA gene (Polymerase Chain Reaction/ PCR), electrophoresis amplicon and sequencing. Bacteria identification was done by comparing the 16S rRNA gene sequence in GenBank. The result showed three bacterias were identified by 16S rRNA have a similarity with Bacillus anthracis strain Ames, Bacillus cereus ATCC 14579, Staphylococcus sciuri subsp. Sciuri strains DSM 20345 and Micrococcus luteus NCTC 2665.